ANALISIS COST EFFECTIVENESS METHOTREXATE VS LEFLUNOMIDE PADA TERAPI RHEUMATOID ARTHRITIS: NARRATIVE REVIEW DAN IMPLIKASI DI INDONESIA - Sita Rizky Mardia; Marisca Evalina Gondokesumo; Jainuri Erik Pratama (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Rheumatoid arthritis (RA) is a chronic inflammatory disease associated with substantial clinical and economic burden. Methotrexate (MTX) is recommended as first-line therapy, whereas leflunomide (LEF) is used as an alternative or adjunctive treatment in specific clinical circumstances. This review aims to analyze the comparison between LEF and MTX from the perspectives of clinical efficacy, health economic assumptions, and their relevance within Indonesia’s National Health Insurance system (Jaminan Kesehatan Nasional, JKN). A narrative review methodology was employed, synthesizing international and national clinical and pharmacoeconomic studies published between 1999 and 2024. The findings indicate that the clinical effectiveness of LEF and MTX is generally comparable; however, most economic models developed in high-income countries rely on cost structures, utility values, and willingness-to-pay (WTP) thresholds that limit their transferability to the Indonesian context. Within the JKN framework, which emphasizes cost containment and budget efficiency, MTX remains the most cost-effective first-line therapy due to its low generic price and adequate clinical effectiveness. LEF retains a role as an alternative or sequential therapy and may be considered an intermediate strategy prior to escalation to substantially more expensive biologic agents. Significant local evidence gaps persist, particularly regarding long-term economic models based on national data, incremental cost-effectiveness ratio (ICER) analyses, and budget impact evaluations within the BPJS system. The development of pharmacoeconomic models grounded in the national payer perspective is therefore essential to support more context-specific and sustainable policy decision-making.